Evaluasi Kinerja Hotel Hijau dengan Metode Green Score dan AHP di Bali - Yana, Anak Agung Istri Anindita Nanda; Normasari, Nur Mayke Eka (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: The purpose of this study is to evaluate the Green Supply Chain performance of hotels in Bali. Research methods: This study uses primary data obtained from questionnaires using a sample of three division heads per hotel and secondary data obtained from past hotel data. The data is processed using excel. Results and discussion: Two hotels obtained results of 66.48 and 75.02. These scores fall into the Average and Good grades. There needs to be some prioritized improvements with SNORM scores below 60 from two different hotels, namely water used, energy used, % suppliers with an EMS or ISO 1400 certification, supplier lead time, delivery item accuracy, and source flexibility. Implication: Recommendations that can be given are the use of PLTS, other water sources, and good communication with suppliers.